HEALTH EDUCATION AS AN AUXILIARY TOOL TO THE PRACTICE OF NURSING CARE (Fiep Bulletin - online, 2012)
This paper came from the concepts created through the subject Health Education, in the Nursing course, at FJN – Faculdade de Juazeiro do Norte (University of Juazeiro do Norte), taught by the professor Stefania Cartaxo Pessoa, who is also the guide of this study. Our research consists of a bibliographical study, based on a sample of 38 articles from the nursing field, which were published in national journals, between 2004 and 2011, analyzed according to the research area, identification of the author and methodological approach. Observing, in the health field, that the difficulties persist, and that the need difficulties persist and the necessity of (re)planning new strategies, seeking for new ways of science production, we found out that knowledge is the main tool that men improves gradually in the social historical process, arising from popular and scientific knowledge. Thus, we tried to map the studies of scientific researchers, which were done in the health education field, seen as a capable solution to change the poor system which is responsible for the well-being of the population, in general. The relevance of our study is imputed by educative actions researches, directed to areas in a vulnerability and degradation situation, built by a profile of scholars who have SOCIAL RESPONSIBILITY and BILATERAL KNOWLEDGE as values.
Keywords: knowledge; health education; nursing